PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. GLOBAL ARDHITYA SWAMANDIRI JAKARTA UTARA - Raihan Hafiz; Sri Mulyani (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of the work environment and work discipline on employee performance at PT. Global Ardhitya Swamandiri. The method used is quantitative. The sampling technique used Saturated Samples and obtained a sample of 60 respondents. The results of this study indicate that work environment has a positive and significant effect on employee performance with a tcount value of 5.739> 1.672 and significant to employee performance by 0.602, work discipline has a positive and significant effect on employee performance with a tcount of 5.793> 1.671 and significant at 0.605. Together work environment and work discipline have a positive and significant effect on employee performance with Fcount 22,735> 2,770 and a significant value of 0.666.